Cultura popular e o modo de vida brincante: costurando linhas de vida na perspectiva das africanidades - Santos, Vanessa Soares (2019)
This research tries to inhabit the existential territory of Brazilian Popular Culture. It was funded by CAPES (Coordination for the Improvement of Higher Education Personnel) in its development, which enabled the research to be carried out. The purpose of this study is to investigate how popular jokes based on Afro-Brazilian civilization values constitute ways of being and being in the world that can inspire the search for lifelines: the bragging way of life in favor of the expansion of power of life. We sought to make this research an experience of the exercise of thought in order to experience thinking without bureaucratizing it, without killing the curiosity, the desire to think, to reinvent. Traditional African cultures have much to teach. They are clues that, in spite of what is instituted as universal thought, other worlds are possible. Thinking about the gibbering way of life and from it, is a form of resistance to a hegemonic model that is instituted. This work is the search for the construction of other ways of being and being in the world that contemplate our needs and affections. It is the resistance against non-pasteurisation of our lives.